Wnt signaling in development and tissue homeostasis - Steinhart, Zachary; Angers, Stephane (Development (Cambridge), 2018)
The Wnt-β-catenin signaling pathway is an evolutionarily conserved cell-cell communication system that is important for stem cell renewal, cell proliferation and cell differentiation both during embryogenesis and during adult tissue homeostasis. Genetic or epigenetic events leading to hypo- or hyper-activation of the Wnt-β-catenin signaling cascade have also been associated with human diseases such as cancer. Understanding how this pathway functions is thus integral for developing therapies to treat diseases or for regenerative medicine approaches. Here, and in the accompanying poster, we provide an overview of Wnt-β-catenin signaling and briefly highlight its key functions during development and adult tissue homeostasis.